2020
DOI: 10.1021/acsmedchemlett.9b00642
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking Studies of Royleanone Diterpenoids from Plectranthus spp. as P-Glycoprotein Inhibitors

Abstract: The development of multidrug resistance (MDR) is a major cause of failure in cancer chemotherapy. Several abietane diterpenes with antitumoral activities have been isolated from Plectranthus spp. such as 6,7-dehydroroyleanone (DHR, 1) and 7αacetoxy-6β-hydroxyroyleanone (AHR, 2). Several royleanone derivatives were prepared through hemi-synthesis from natural compounds 1 and 2, to achieve a small library of products with enhanced anti-P-glycoprotein activity. Nonetheless, some derivatives tend to be unstable. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…On the contrary, royleanones 1–4 showed the same efficacy in sensitive and MDR cancer cells implying that they could not be P-gp substrates. Moreover, Isca et al (2020) based on docking simulations also suggest that derivatives 4 and 23 act as non-competitive efflux inhibitors.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…On the contrary, royleanones 1–4 showed the same efficacy in sensitive and MDR cancer cells implying that they could not be P-gp substrates. Moreover, Isca et al (2020) based on docking simulations also suggest that derivatives 4 and 23 act as non-competitive efflux inhibitors.…”
Section: Resultsmentioning
confidence: 93%
“…Based on the FAR (values above 1.50 indicate P-gp inhibition) and SI (values above 20 account for P-gp inhibition), we could see that only derivatives 4 and 23 have the ability to inhibit P-gp activity, with FAR values of 1.71 and 2.10, respectively, and SI of 21.60 and 26.50, respectively. Additionally, derivative 23 has shown a comparable inhibitory potential to the well-known P-gp inhibitor, Dexverapamil (FAR 2.13 and SI 26.90) ( Isca et al, 2020 ). A recent study used molecular docking and molecular dynamics to explore the interaction of derivatives 4 and 23 with P-gp and suggested that the presence of aromatic moieties increases the binding affinity of royleanone derivatives toward P-gp ( Isca et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations